Karyomegalic interstitial nephritis as a rare cause of kidney graft dysfunction: case report and review of literature - Fatma El-Husseiny Moustafa; Eman Nagy; Salwa Mahmoud Elwasif; Mohamed Sobh (BMC Nephrology, 2023)
Abstract Karyomegalic interstitial nephritis (KIN) is a rare cause of chronic interstitial nephritis characterized by enlarged renal tubular epithelial nuclei. The first case of KIN reported in a kidney graft was in 2019. Here, we report the first case of KIN in 2 brothers receiving kidneys from 2 different unrelated living donors. A male kidney transplant recipient with focal segmental glomerulosclerosis as the original kidney disease presented with graft impairment and proteinuria, and graft biopsy revealed KIN. This patient had a brother who was also a kidney transplant recipient and had one episode of graft impairment and was diagnosed with KIN as well.